Factor Influencing Young Consumers’ Intention to Purchase Organic Food - Yi Joe Kang,; Chan, Shiau Wei; Fadillah Ismail,; Rosmaini Tasmin,; Md Fauzi Ahmad, (Research in Management of Technology and Business, 2024)
Following the researcher's preliminary study involving customers of Aeon stores in Batu Pahat, the research findings revealed significant price disparities between organic food and conventional food in Malaysia, with organic food being considerably more expensive, often ranging from 100% to 300% higher in price. When national statistics were compared, it was observed that most deaths in Malaysia were attributed to non-communicable diseases (NCDs), specifically diseases related to the circulatory system. In that study, the researcher aimed to conduct an initial investigation that focused on examining the level of awareness of organic food among young consumers. Additionally, the study sought to identify the various factors that influenced the purchase intentions of young consumers toward organic food at AEON SDN BHD Batu Pahat. The study targeted customers who had previously bought organic products at AEON SDN BHD in Batu Pahat. The sample size for this study is 320 respondents who participated in this research. It utilized a questionnaire as its research tool and analyzed the gathered data through IBM's SPSS Statistics version 27. Both research objectives and the four hypotheses were satisfactorily fulfilled. The initial aim to gauge awareness of organic products revealed a high level of recognition, albeit influenced by various factors impacting young consumers' inclination to buy organic food. Additionally, the second objective pinpointed determinants affecting young consumers’ intent to purchase organic products, demonstrating significant correlations with their purchase intentions. This study was significant in the context of Malaysia as it provided valuable evidence that could contribute to a better understanding of organic food.